PRIVATE SPEECH IN ADULT FOREIGN LANGUAGE ACQUISITION: MECHANISMS, IMPLICATIONS, AND PATTERNS AMONG TERTIARY LEARNERS - Rahayu Prasetyaningsih; Ernitasari Mulyadi; Dewi Rara Amiati; Hasriana (Tadulako University, 2025)
This research investigates the mechanisms of private speech in adult foreign language acquisition, particularly English language, focusing on how tertiary learners utilize self-directed talk to manage cognitive load during motor-language tasks. The study aims to identify the specific triggers, behavioral patterns, and self-regulatory functions of private speech when learners are required to coordinate physical actions with real-time English narration. Employing a qualitative phenomenological design, the study involved five sophomore students at Universitas Muhammadiyah Palu who participated in an Action-Sequence Protocol followed by Video-Stimulated Recall Interviews (SRI). Data were analyzed through observation of behavioral markers and thematic condensation of interview reflections. Results indicate that private speech acts as a vital cognitive bridge, manifesting through three primary functions: iterative planning for task management, affective self-soothing to mitigate frustration, and spontaneous error monitoring. Findings reveal a dichotomy in strategies, where some learners externalize cognitive load through audible whispering while others internalize it through prolonged pausing. These results prove that hesitation and mumbling in adult learners are sophisticated self-regulatory strategies rather than linguistic deficiencies. The study implies a necessary paradigm shift in tertiary pedagogy, suggesting that educators should recognize and encourage private speech as a legitimate scaffolding tool to reduce speaking anxiety and foster learner autonomy in English language context. These insights establish a foundation for future exploration into culturally integrated speaking tasks and longitudinal pedagogical interventions. Keywords: Private Speech; Action-Sequence; Foreign Language Acquisition; Tertiary Learners; Self-Regulation